Gender of the genus Botrylloides Milne Edwards (1841) [Tunicata: Ascidiacea] - Ryland, John S (Zootaxa, 2015)
Milne Edwards (1841) introduced Botrylloides listing species with both feminine and neuter word endings. The International Code on Zoological Nomenclature, however, indicates that generic names ending -oides should be masculine unless the introducing author unambiguously indicated a different gender. The resulting uncertainty has caused prolonged confusion over the correct gender of Botrylloides. It is here affirmed that Milne Edwards did not provide a clear indication of gender and the general rule of the International Code applies: Botrylloides has masculine gender. The type species is B. rotifer Milne Edwards (its ending corrected from the feminine B. rotifera).